The Use of a Venous Catheter as a Stent for Treatment of Acquired Punctal and Canalicular Stenosis. Issue 8 (November 2019) - Meduri, Alessandro; Inferrera, Leandro; Tumminello, Giuseppe; Frisina, Rino; Forlini, Matteo; Kaufman, Stephen; Aragona, Pasquale
Abstract : Purpose: The aim of this study was to describe a simple technique to insert a venous catheter as a stent for the treatment of acquired punctal and canalicular stenosis. Methods: We performed this technique using a central venous catheter as a stent for the treatment of acquired punctal and canalicular stenosis. Results: The results show the easy availability of the material used for the intervention, its easy execution, and the low costs of materials. The goal of this technique is to have a lacrimal dot dilated and canalicular duct easy to irrigate. Conclusion: The use of a venous catheter as a stent for treatment of acquired punctal and canalicular stenosis seems to be simple, safe, repeatable, and noninvasive.